Raman spectroscopy of fingernails: A novel tool for evaluation of bone quality?. Issue 5 (2010) - Cummins Cummins, N. M. N. M.; Day Day, J. C. C. J. C. C.; Wren Wren, A. A.; Carroll Carroll, P. P.; Murphy Murphy, N. N.; Jakeman Jakeman, P. M. P. M.; Towler Towler, M. R. M. R.
Abstract : Raman data from human fingernails has been analysed to determine if a relationship exists between spectral features and bone quality. Previous work demonstrated a relationship between the manually determined intensity of the disulphide peak (Bone Quality Test; BQT) and osteoporotic fracture. A computer program is now described that automates the BQT determination for large sample-sets. In this study the ability of the automated BQT to discriminate between fractures and controls was compared to that of bone mineral density (BMD) and biomarkers of bone remodelling. Females aged 18–67 years participated in the study ( n ═ 159). Fingernails were analysed using Raman spectroscopy. Lumbar and Femoral BMD was measured by dual energy X-ray absorptiometry (DXA). Fasting venepuncture samples were analysed for osteocalcin and CTx (collagen C-telopeptides) by electrochemiluminescence. No correlation was found between the BQT and BMD or the biomarkers. The BQT and BMD were found to be equally accurate in identifying subjects with a history of fracture ( p < 0.01) and both outperformed osteocalcin and CTx. It appears that keratin and collagen are related structural proteins that require disulphide bonding for stability. Therefore, these preliminary results suggest that Raman spectroscopy of keratin may have potential as a diagnostic tool for screening bone quality in large populations.